Connexin 43 Channels in Osteocytes Regulate Bone Responses to Mechanical Unloading - Zhao, Dezhi; Liu, Ruofei; Li, Guobin; Chen, Meng; Shang, Peng; Yang, Hui; Jiang, Jean X.; Xu, Huiyun (Frontiers in Physiology, 2020)
Connexin (Cx) 43-forming gap junctions and hemichannels mediate communication between osteocytes and adjacent cells or the extracellular environment in bone, respectively. To investigate the role of two channels in response to unloading, two transgenic mouse models overexpressing dominant-negative Cx43 predominantly in osteocytes driven by a 10-kb dentin matrix protein 1 (DMP1) promoter were generated. The R76W mutation results in gap junctions inhibition and enhancement of hemichannels, whereas the Δ130-136 mutation inhibits both gap junctions and hemichannels. Both mutations showed cortical bone loss with increased endocortical osteoclast activity during unloading. Increased periosteal osteoclasts with decreased apoptotic osteocytes were observed only in R76W mice. These findings indicate that inhibiting osteocytic Cx43 channels promotes bone loss induced by unloading, mainly in the cortical area; moreover, hemichannels protect osteocytes against apoptosis and promote periosteal bone remodelling, and the gap junctions modulating endocortical osteoclast activity in response to unloading.